Guía psicopedagógica basada en técnicas de danza bhangra para estimular la coordinación motora en alumnos de 11 a 14 años con síndrome de down de la Fundación El Triángulo - Mateus Basantes, María Paula (2020)
The main objective of this research work is to demonstrate the importance of techniques based on Bhangra dance as a psychopedagogical strategy to stimulate the coordination and psychomotor skills of students who are in the transition stage corresponding to the ages of 11 to 14 years they present. Down syndrome, belonging to the El Triángulo Foundation, located in the city of Quito. The research methodology that is intended to be used in this study is a qualitative approach, which is based on the analysis and description of reviewed literature on topics such as: Symptomatology of Down Syndrome, prevalence, evolution of the syndrome, areas of learning affected by the syndrome, motor coordination in Down syndrome and about Bhangra dance. In addition, the following work raises the use of quantitative evaluation techniques, such as the index nose test and the Fukuda test. The same ones that allow obtaining relevant results to carry out the research and at the same time will allow identifying the need presented by the population studied regarding the shortcomings in motor coordination.